FORMULATION AND CHARACTERIZATION OF PH-INDUCED IONIC GELATION CIMETIDINE ORAL IN SITU GEL FOR TARGETED GASTRIC DELIVERY - Chetan Kumar Shettya; Sheeba F. Roseleta Navyashree Gowdaa
Cimetidine is an orally administered anti-ulcer medication. This study aims to develop a gastro-retentive in situ gel containing the drug to enhance its oral bioavailability and provide prolonged release. The gel was prepared by incorporating an emulsion into a polymeric solution, resulting in a floating in situ gel. The prepared solution was evaluated for pH, viscosity, drug content and in vitro drug release. The in vitro drug release studies demonstrated good drug release, ranging from 61.64% to 84.4% over 10 h. The best formulation, identified as F4, exhibited an in vitro drug release, of 68.64%. The correlation coefficient values from kinetic equations indicated that drug release from the formulations followed a Higuchi first-order release mechanism. The approved formulations met all the criteria for developing a gastro-retentive in situ gel system that gelled quickly and floated within the stomach$1 (Bs pH range.s